Fulminant Guillain–Barré Syndrome and Spontaneous Intraventricular Hemorrhage: A Case Report and Literature Review - Hu, Jun; Luo, Xiaoqian; Wang, Yu; Prado, Eric; Fu, Qinghui; Shao, Anwen (Frontiers in Neuroscience, 2020)
Guillain–Barré syndrome (GBS) is an acute, immune-mediated inflammatory peripheral polyneuropathy that is characterized by flaccid paralysis. A few cases have reported that GBS can be caused by head trauma or neurosurgery, but it has never been associated with intraventricular hemorrhage. Here, we report an uncommon case of fulminant GBS that occurred after spontaneous intraventricular hemorrhage. A 73-year-old woman was admitted to the hospital after sudden unconsciousness and vomiting. A head computed tomography (CT) scan following the incident showed a newly developed intraventricular hemorrhage, which led to an immediate ventriculostomy. After five days, the endotracheal tube was removed. Two days later, the external ventricular drainage tube was also removed. At this time, the patient was alert and the neurological examination was normal. However, the patient suddenly presented with acute respiratory failure and bilateral limb weakness 3 days later. An analysis of the patient’s cerebrospinal fluid (CSF) revealed that albuminocytologic dissociation was present. The patient was treated with intravenous immunoglobulin (0.4 g/kg/day) for 5 days. Despite timely medical intervention in the hospital, the patient passed away 2 months later. After a cerebral hemorrhagic injury, limb and respiratory muscle weakness can occur on occasion in the ICU. In this context, the potential involvement of GBS should not be ignored. Importantly, the pathogenic mechanism of GBS has been discussed for over a century and it still remains a mystery. We speculate that the TLR4/NF-κB signaling pathway may be involved in the pathogenesis of GBS following intraventricular hemorrhage. The prognosis of most patients with GBS is usually good, but cerebral hemorrhage and mechanical ventilation may serve as risk factors that exacerbate the condition. This case is reported to remind clinicians to consider the possibility of GBS when patients present limb and respiratory muscle weakness after intraventricular hemorrhage, and to provide a starting point to discuss potential mechanisms of GBS after intraventricular hemorrhage.